Tailoring of graphene–organic frameworks membrane to enable reversed electrical-switchable permselectivity in CO2 separation. (September 2021) - Widakdo, Januar; Huang, Tsung-Han; Subrahmanya, T.M.; Austria, Hannah Faye M.; Hung, Wei-Song; Wang, Chih-Feng; Hu, Chien-Chieh; Lee, Kueir-Rarn; Lai, Juin-Yih
Abstract: Membrane separation has been an efficient and energy saving technique in dealing with greenhouse gases, but the traditional membrane designs might not be able to handle the concomitant environmental pollution due to their fixed properties. Correspondingly, the use of an active-responsive smart membrane appears to be a new trend for membrane development in the coming future, which shows great potential to deal with the obstacles. In this research, we demonstrate a smart graphene-organic framework membrane to enable reversed electrical-switchable permselectivity in CO2 separation. The addition of polydopamine (PDA) to the polyvinylidene fluoride/Graphene (PVDF/G) membranes was done to (i) induce the β-phase of PVDF, since –NH2 -functionalized graphene has specific interactions (dipole induced dipole interaction) between graphene-PDA and PVDF; (ii) modify the organic PVDF-inorganic graphene interface; and (iii) facilitate CO2 selective separation. Permeability and permselectivity was increased after applying voltage that resulted in the increase of gas permselectivity in response to the lowest applied voltage range (0–3 V) to the membrane. Digital image correlation method depicted the response of the membrane to voltage and proved that the membrane has high piezoelectric properties that is switchable. Furthermore, PALS studies confirmed the free volume and interlayers in the membrane. This membrane has unique properties because the pore changes from bimodal to single pore distribution. Graphical abstract: Image 1 Highlights: Membrane exhibits selectivity switchable CO2 separation performance to an external stimulus (applied voltage). Digital image correlation method depicted response of the membrane by voltage and proved that the membrane has high piezoelectric properties and switchable. Atomic-level positron annihilation lifetime spectroscopic studies confirmed the free volume and interlayers in the membrane. In response to the electrical stimuli applied to the system, the pore changes from bimodal to a single pore distribution.